2018
DOI: 10.1530/erc-18-0222
|View full text |Cite
|
Sign up to set email alerts
|

The IGF pathway is activated in insulinomas but downregulated in metastatic disease

Abstract: Clinical and molecular studies have implicated epidermal growth factor receptor (EGFR), insulin-like growth factor (IGF) and target of rapamycin (mTOR) signaling pathways in the regulation of pancreatic neuroendocrine tumor (PanNET) growth. Interpretation and comparison of these studies is complex due to clinical and molecular tumor heterogeneity. We therefore focused in this study on insulinomas, which we examined for mRNA and protein expression of EGFR, IGF and mTOR signaling pathway components by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Interestingly, aggressive insulinomas often only have sporadic or focal insulin expression, and some studies have reported cases lacking immunohistochemical insulin expression, although this might be a sampling effect in larger tumors (de Sa et al 2007, Yu et al 2017, Andreassen et al 2019. In line with these findings, decreased INS mRNA expression (relative to normal betacells) was seen in aggressive vs indolent insulinomas (Henfling et al 2018). Aggressive insulinomas are multihormonal in 50% of cases compared to 25% of indolent insulinomas (Kapran et al 2006), and glucagon is expressed more often in aggressive cases (de Sa et al 2007, Andreassen et al 2019.…”
Section: Indolent Vs Aggressive Insulinomasmentioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, aggressive insulinomas often only have sporadic or focal insulin expression, and some studies have reported cases lacking immunohistochemical insulin expression, although this might be a sampling effect in larger tumors (de Sa et al 2007, Yu et al 2017, Andreassen et al 2019. In line with these findings, decreased INS mRNA expression (relative to normal betacells) was seen in aggressive vs indolent insulinomas (Henfling et al 2018). Aggressive insulinomas are multihormonal in 50% of cases compared to 25% of indolent insulinomas (Kapran et al 2006), and glucagon is expressed more often in aggressive cases (de Sa et al 2007, Andreassen et al 2019.…”
Section: Indolent Vs Aggressive Insulinomasmentioning
confidence: 84%
“…In contrast to non-functioning PanNETs, tumor grade based on mitosis count per high power field or Ki-67 staining index is not univocally associated with aggressive behavior (Alkatout et al 2015, Yu et al 2017, Henfling et al 2018, Andreassen et al 2019, Sada et al 2021. Importantly, even grade 1 tumors may show aggressive behavior (Wild et al 2011, Hackeng et al 2020; therefore, tumor grade cannot reliably be used clinically for excluding aggressive behavior.…”
Section: Indolent Vs Aggressive Insulinomasmentioning
confidence: 98%
See 1 more Smart Citation
“…Henfling et al found decreased expression of EGFR and mTOR pathway components, and increased expression of IGF2 in insulinoma cells [72]. Again, however, because those results were compared to normal pancreatic islets, it was not possible to determine whether this was associated with the tumour state or specifically with insulinomas.…”
Section: Original Papermentioning
confidence: 97%
“…Moreover, in a mouse model of multistage carcinogenesis induced by the SV40 large T antigen in pancreatic beta-cells, IGF2 was increased and contributed to insulinoma development (103). Recently, studies have shown that the IGF pathway is activated in insulinoma (104). Glutamine can also stimulate biosynthesis and secretion of IGF2 in mouse insulinoma cells, which regulate beta-cell mass and function in an autocrine manner (105).…”
Section: Insulinomamentioning
confidence: 99%